2017
DOI: 10.3178/hrl.11.134
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rice cultivation on evapotranspiration in small seasonal wetlands of north-central Namibia

Abstract: This paper aims to evaluate the effect of mixed-cropping of rice and upland crops on evapotranspiration (ET) in a small seasonal wetland in the north-central Namibia. Meteorological observations were conducted in the experimental sloped field, which simulated the cultivation of both rice in a wetland environment and upland crops in the surrounding rain-fed area, and included a reference wetland with natural vegetation. During cultivation, ET from the rice field was similar to that from the wetland. However, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The experiments were conducted on the lower part of a slope in the field to simulate cultivation in small, seasonal wetlands. An experimental field was set up, which was 80 m × 160 m in size, with an artificial slope of 1/80 [24,25]. Weather data were obtained from the Southern African Science Service Centre for Climate Change and Adaptive Land Management (SASSCAL) website (http://www.sasscalweathernet.org/weatherstat_monthly_we.php, accessed date: 10 March 2021).…”
Section: Study Sitementioning
confidence: 99%
“…The experiments were conducted on the lower part of a slope in the field to simulate cultivation in small, seasonal wetlands. An experimental field was set up, which was 80 m × 160 m in size, with an artificial slope of 1/80 [24,25]. Weather data were obtained from the Southern African Science Service Centre for Climate Change and Adaptive Land Management (SASSCAL) website (http://www.sasscalweathernet.org/weatherstat_monthly_we.php, accessed date: 10 March 2021).…”
Section: Study Sitementioning
confidence: 99%
“…e advent of upland NERICA rice [16] has created an opportunity to extend rice production into semiarid, Sub-Saharan agroecosystems [6,[17][18][19]. Recent studies in northern Namibia have demonstrated that rice can be cultivated in the local seasonal wetlands [9,10,20], without modifying the water environment in the system [21][22][23]. Currently, rice farming in the country was done by few producers; thus, the wetlands are traditionally used for seasonal livestock grazing and fishing [12,24], despite the high demand for homegrown rice [6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, since the wetlands are seasonal, most of the water is eventually lost through evaporation and by deep percolation. Increasing rice cultivation in the local wetland ecosystems has the potential to offer new rice-based foodstuffs and a new cropping land area, complementary to the existing arable land used for the production of traditional dryland crops, while simultaneously conserving the local water environment [23].…”
Section: Introductionmentioning
confidence: 99%
“…The response and feedback mechanism of hydrological wetland ecosystem under the influence of global change and human activities is the focus and frontier issue of common concern in the international community (Guo, 2018). Consolidation and deformation characteristics of soft rock foundation in hydrological wetland environment are affected by many factors, such as physical and mechanical properties of soft rock and soil, sludge thickness of hydrological wetland, loading capacity, loading mode and field environment (Xu et al, 2017;Kotani et al, 2017). In the hydrological wetland area, in order to carry out the construction of soft rock foundation smoothly, cofferdams are built on both sides of most sections before foundation treatment, and counter-pressure barriers are built between cofferdams and roads.…”
Section: Introductionmentioning
confidence: 99%